The Decentralized Administrative Concept. A Report to the Board of Trustees - Youngerman, Stephenson S., Jr.; Boise City Independent School District, ID. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This report presents a model for participation by the community, teachers, and administrators in the decisionmaking process. The report tells how the Boise, Idaho, school district used a systems approach to set up a decentralized decisionmaking system. The duties of various persons in the system (with emphasis on the importance of the role of the principal and his staff) are outlined. An appendix contains a master planning model and a design of the Maple Grove Elementary School planning system. (JF)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Organization; Administrator Role; Boards of Education; Community Involvement; Cooperative Planning; Decentralization; Decision Making; Policy Formation; Principals; Systems Approach; Teacher Participation